(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Scintillation characteristics such as spectra, decay times and yields of Cu- and Ag- doped ZnSXSel-X solid solutions, and some other compounds have been measured under X-rays excitation. Certain investigated materials show a high light yield in the long wavelength region and adequate kinetic properties. It is shown that the light yield can be increased for compounds synthesized at optimal conditions. The measurements have been held in St. Petersburg State Polytechnical University, Petersburg, Russia تحت تأثير الأشعة السينية، تم قياس مميزات أطياف التألق وأزمنة التفكك لعناصر النحاس والفضة المضافة إلى المحاليل الصلبة وكذلك بعض المركبات الأخرى المستخدمة. أظهرت الدراسة على بعض المواد حدوث (تحرر) تألق ضمن مجال طول موجي واسع وبميزات طاقية كافية. وتبين أن طاقة الضوء المتحرر يمكن زيادتها في بعض المركبات المصنعة (المحضرة) عند شروط تركيبية مثالية. أجريت القياسات في جامعة بطرس بورغ التكنولوجية الحكومية – بطرس بورغ – روسيا.